Pelatihan Pembuatan Desinfektan Skala Rumah Tangga di Kelurahan Kandang Limun Kota Bengkulu - Ratu Eva Febriani; Muhammad Rusdi; Retno Agustina Ekaputri; Novi Tri Putri (UNIB Press, 2023)
Health is a precious basic human right. Prevention is better than cure, the jargon is common among the public. However, in its implementation, this is difficult to apply due to various factors, one of which is limited knowledge about how to prevent disease. People in Kandang Limun Village in Bengkulu City are included in the level of urban communities that are identical to living in dense settlements and relatively large populations with diverse characteristics. One of the problems faced by urban residents is the spread of infection from microorganisms (germs and viruses) originating from the surface of objects such as floors, tables, chairs, etc. The use of disinfectants is one solution to overcome these problems. The limited household budget to provide specially purchased disinfectants can be overcome by making their own disinfectants from materials at home.